Comprehensive review of additively manufactured biodegradable magnesium implants for repairing bone defects from biomechanical and biodegradable perspectives - Wang, Zhengguang; Liu, Bingchuan; Yin, Bangzhao; Zheng, Yufeng; Tian, Yun; Wen, Peng (Frontiers in Chemistry, 2022)
Bone defect repair is a complicated clinical problem, particularly when the defect is relatively large and the bone is unable to repair itself. Magnesium and its alloys have been introduced as versatile biomaterials to repair bone defects because of their excellent biocompatibility, osteoconductivity, bone-mimicking biomechanical features, and non-toxic and biodegradable properties. Therefore, magnesium alloys have become a popular research topic in the field of implants to treat critical bone defects. This review explores the popular Mg alloy research topics in the field of bone defects. Bibliometric analyses demonstrate that the degradation control and mechanical properties of Mg alloys are the main research focus for the treatment of bone defects. Furthermore, the additive manufacturing (AM) of Mg alloys is a promising approach for treating bone defects using implants with customized structures and functions. This work reviews the state of research on AM-Mg alloys and the current challenges in the field, mainly from the two aspects of controlling the degradation rate and the fabrication of excellent mechanical properties. First, the advantages, current progress, and challenges of the AM of Mg alloys for further application are discussed. The main mechanisms that lead to the rapid degradation of AM-Mg are then highlighted. Next, the typical methods and processing parameters of laser powder bed fusion fabrication on the degradation characteristics of Mg alloys are reviewed. The following section discusses how the above factors affect the mechanical properties of AM-Mg and the recent research progress. Finally, the current status of research on AM-Mg for bone defects is summarized, and some research directions for AM-Mg to drive the application of clinical orthopedic implants are suggested.